Predições do uso e cobertura da terra e seus impactos na erosão do solo na Bacia do Alto Paraguai - Nunes, Nivalda da Costa (2024)
The Upper Paraguay Basin (BAP), located in the states of Mato Grosso and Mato Grosso do Sul, encompasses the biomes Cerrado, Amazon, and Pantanal. Despite the importance of these biomes, the BAP has been experiencing significant changes in land use and cover, resulting in substantial impacts on the Pantanal. In this context, this study analyzed land use and cover changes in the Upper Paraguay Basin between 1985 and 2020, as well as projections for 2030, 2040, and 2050, with estimates of soil losses for some analyzed years, including future projections. The land use and cover analysis used data from the MapBiomas project and Markov Chain-based modeling for future projections. The soil loss estimates were made using the USLE (Universal Soil Loss Equation) model, composed of natural factors (erosivity, erodibility, and topography) and anthropogenic factors (land use and cover, and conservation practices). The simulation for the year 2020 presented an overall Kappa index of 0.7521. Analyzing the BAP from 1985 to 2020, a significant reduction in water bodies, flooded fields, and swampy areas was observed, while agriculture expanded on the plateau and pastures increased on both the plateau and plain. Projections indicate that by 2050, water bodies will occupy only 0.5% of the BAP, a loss of 93.5% since 1985, representing a serious environmental risk to the Pantanal. The average annual erosion of the BAP sub-basins ranged from 4,990.12 MJ mm h-1 ha-1 year-1 to 11,116.31 MJ mm h-1 ha-1 year-1, with the highest averages in the Alto Rio Cuiabá, Corrente, and Taquari basins. The average erodibility across the basin was 0.0189 t h MJ-1 mm-1. The average LS factor value was 0.90 in the BAP, with the lowest averages in the sub basins located in the plain. The highest CP factor values were in the anthropogenic activities developed in the BAP, which increased in area each year analyzed. The average soil loss in the BAP was 3.66 t ha-1 year-1 in 1985, reaching an average of 5.55 t ha-1 year-1 in 2020. Observing the sub-basins, it is evident how anthropogenic activities influence soil loss values, especially in regions where natural factors favor soil loss, such as high LS and R Factor values. The São Lourenço sub-basin had the highest real erosion values among the other basins, a fact explained by its natural propensity for erosion, being the basin with the highest LS Factor value and high average erosivity (R Factor), apart from the constant anthropic activity. These results demonstrate how much the BAP is being affected by changes in land use and cover over the years, due the increase in anthropogenic activities such as agriculture and pasture. Additionally, these changes are occurring very quickly, requiring immediate actions.